RISK TAKING AND ENTREPRENEUR EDUCATION IN SHAPING ENTREPRENEUR INTENTION - Baistaman, Julaina; Abu Bakar, Hatinah; Wan Mustapha, Wan Masnieza; Mat Nawi, Farahiyah Akmal (International Journal of Accounting, Finance and Business, 2024)
This study examines student entrepreneurial intention affected by risk taking and entrepreneurial education among undergraduate Universiti Teknologi MARA (UiTM) students. This study applied quantitative and cross-sectional design of 317 students from UiTM across Malaysia. The findings indicate positive relationship between risk taking and entrepreneurial education in shaping students’ intention to be entrepreneurs in future.